Sumbangan Internalisme dan Eksternalisme dalam Konsep Ketuhanan - Untara Simon (Arete, 2022)
Internalism and externalism are closely related to the issue of knowledge justification. There are fundamental differences between the two streams in the epistemology. However, both agree that to be true, knowledge must be justified. For internalism, this justification is sufficient from within: if it is based on memory, conclusions on various opinions and sensory perceptions of the subject of the knower have rational and reasonable justifications, then the conclusion is true. While for externalism, justification must take into account the validity of the process of achieving knowledge so that the environment, history and social context associated with that knowledge must be taken into account in determining the truth of a conclusion.This paper will try to answer the following questions: Related to the internalism-externalism debate, how can theology be classified? Is it true that theology falls into the category of internalism because God, the object of knowledge in theology, is something that has never been encountered by anyone, cannot be sensed and cannot be objectified? What are the implications of this classification of theology for theology itself? How does this debate make a special contribution to theology? Key Words: Epistemology, Internalism, Externalism, Theodicy.